Does Disclosure About the Common Factors Affect Laypersons' Opinions About How Cognitive Behavioral Psychotherapy Works? - Blease, Charlotte R.; Kelley, John M. (Frontiers in Psychology, 2018)
Background: Written and online information about cognitive-behavioral therapy (CBT) prioritizes the role of specific techniques (e.g., cognitive restructuring) and typically omits discussion of ‘common factors’ (e.g. the working alliance, or therapist empathy). However, according to extensive psychotherapy process research the common factors may be important mediators of client improvement. Objectives: This study aimed to assess lay opinions about the role of specific and common factors in CBT for depression. We also aimed to determine how different client disclosure processes might affect lay opinions about the relative importance of specific and common factors in CBT. Methods: We conducted a web-based experiment involving a sample of US participants who had never undergone psychotherapy. All participants were presented with similar vignettes describing an individual suffering from depression whose doctor recommends CBT. Participants were randomized to read one of six vignettes created in a 2x3 factorial design that crossed client gender with type of informed consent (Standard CBT Disclosure vs. Common Factors and CBT Disclosure vs. No Disclosure). Results: Disclosure type had a significant effect on participants’ ratings of Common and Specific factors in psychotherapy. As compared to the CBT disclosure, participants allocated to the Common Factors disclosure rated Empathy and Positive Regard as significantly more important to treatment outcome, and rated the Specific factors of CBT as significantly less important to outcome. There were no significant differences between No Disclosure and Standard CBT Disclosure, and these participants rated Specific factors of CBT and the Working Alliance as more important components in treatment, and Empathy and Positive Regard as less important. Conclusions: The content of information disclosures influences lay opinions about the importance of specific and common factors in CBT. Further research should investigate ethically acceptable disclosures to CBT and other forms of psychotherapy, including whether disclosure practices affect treatment outcome.